Russians, Jews, and the pogroms of 1881 - 1882 - Klier, John (Cambridge Univ. Press, 2011)
"Anti-Jewish pogroms rocked the Russian Empire in 1881-2, plunging both the Jewish community and the imperial authorities into crisis. Focusing on a wide range of responses to the pogroms, this book offers the most balanced and comprehensive study of the crisis to date. It presents a nuanced account of the diversity of Jewish political reactions and introduces a wealth of new sources covering Russian and other non-Jewish reactions to these events. Seeking to answer the question of what caused the pogroms' outbreak and spread, the book provides a fuller picture of how officials at every level responded to the national emergency and irrevocably lays to rest the myth that the authorities instigated or tolerated the pogroms. This is essential reading not only for Russian and Jewish historians but also for those interested in the study of ethnic violence more generally"--Provided by publisher